Susceptibility Weighted Imaging as a Useful Imaging Adjunct in Hemichorea Hyperglycaemia - Ferry Dharsono; Andrew Thompson; Jolandi van Heerden; Andrew Cheung (Case Reports in Radiology)
Hyperglycaemia with hemichorea (HGHC) is an unusual clinical entity that can be associated with corpus striatum hyperintensity on T1-weighted (T1W) magnetic resonance imaging (MRI) sequences. We report the utility of the susceptibility weighted image (SWI) sequence and the filtered phase SWI sequence in the imaging assessment of HGHC.